ANALISIS DEFECT PADA KEMASAN PACKAGING DENGAN METODE NEW 7 QUALITY MANAGEMENT TOOLS - Fransaputra, Jonathan; Salomon, Lithrone Laricha; Andres (Jurnal Mitra Teknik Industri, 2025)
Product quality is a crucial aspect in the manufacturing industry, especially in the packaging industry, which plays a significant role in maintaining consumer perception and company image. Gummed tape department is one of the production units facing the challenges related into various defect issues. These defect impacts production efficiency, increasing costs, and reducing customer trust. This research aims to identify the problems, analyze the root causes, and propose solutions to address them. the research employs the New Seven Quality Management Tools, including Affinity Diagram, Relations Diagram, Tree Diagram, Matrix Diagram, Matrix Data Analysis, Arrow Diagram and Process Decision Program Chart. The analysis results indicate that the main factors consist of 5 aspects, Human, Material, Machine, Process, and Environment. The problems found are process inconsistencies, Inappropriate work environment, non-standard materials, no inspection and others. Suggestions for improvement that can be given are in the form of updating SOP, providing training for operators, adjusting the work environment, conducting inspections between processes.